Windsock memory COnditioned RAM (CO‐RAM) pressure effect: Forced reconnection in the Earth's magnetotail. Issue 8 (13th August 2014) - Vörös, Z.; Facskó, G.; Khodachenko, M.; Honkonen, I.; Janhunen, P.; Palmroth, M.
Abstract Magnetic reconnection (MR) is a key physical concept explaining the addition of magnetic flux to the magnetotail and closed flux lines back‐motion to the dayside magnetosphere. This scenario elaborated by Dungey (1963) can explain many aspects of solar wind‐magnetosphere interaction processes, including substorms. However, neither the Dungey model nor its numerous modifications were able to explain fully the onset conditions for MR in the tail. In this paper, we introduce new onset conditions for forced MR in the tail. We call our scenario the "windsock memory conditioned ram pressure effect." Our nonflux transfer‐associated forcing is introduced by a combination of the large‐scale windsock motions exhibiting memory effects and solar wind dynamic pressure actions on the nightside magnetopause during northward oriented interplanetary magnetic field (IMF). Using global MHD Grand Unified Magnetosphere Ionosphere Coupling Simulation version 4 simulation results, upstream data from Wind, magnetosheath data from Cluster 1 and distant tail data from the two‐probe Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun mission, we show that the simultaneous occurrence of vertical windsock motions of the magnetotail and enhanced solar wind dynamic pressure introduces strong nightside disturbances, including enhanced electric fields and persistent vertical cross‐tail shear flows. These perturbations, associated with a stream interaction region in the solar wind, drive MR in the tail during episodes of northward oriented interplanetary magnetic field (IMF). We detect MR indirectly, observing plasmoids in the tail and ground‐based signatures of earthward moving fast flows. We also consider the application to solar system planets and close‐in exoplanets, where the proposed scenario can elucidate some new aspects of solar/stellar wind‐magnetosphere interactions.